Los Scholia de Juan de Mal Lara al progymnasma de la fábula de Aftonio - Arcos Pereira, Trinidad; Cuyás de Torres, María Elisa (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
The Latin translations and the commentaries to Aphthonius’ Progymnasmata, used as a handbook for elementary teaching of rhetoric, had a great diffusion all over Europe during the sixteenth century. Among these we have Juan de Mal Lara’s Scholia, published in Seville in 1567. In this paper we will study the commentary of this humanist from Seville to Aphthonius’ Progymnasmata of the fable and will compare it to the ones published formerly by three humanists who enjoyed a great prestige at the moment: Reinhard Lorich, his friend and classmate in Salamanca, the Brocense, and his master, Francisco Escobar, in order to establish Mal Lara’s position among the sixteenth-century commentators, his dependence and originality. Our work allows us to conclude that, although Mal Lara is definitely indebted to the tradition, he also presents particular features absent in the former scholiasts such as the proposal of a new typology of the fable, his selection of authors and examples, the type of recommended exercises and, especially, his pedagogic concern for facilitating the learning of rhetoric to his students.